Positive and Negative Aspects of the Impact of Technogenic Civilization on Human Knowledge (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A comprehensive understanding of the problems that arise in modern culture and civilization can be seen at the intersection of interdisciplinary approaches in science, in the development of new research methodologies enriched by developments in the field of interrelated disciplines, as well as in the interaction of science and science. Religion allows us to prevent the blind actions of people by informing them about the consequences that negatively affect the lives of people in certain regions and on the whole planet. Through this article is a theoretical analysis of the influence of man-made civilization on the dynamics of human knowledge. Based on the goal, the following tasks were defined: Analyzing the concept of man-made civilization; Studying the impact of man-made civilization on the dynamics of human knowledge ; Identify the positive and negative aspects of man-made civilization.